Oligarchic family control, social economic outcomes, and the quality of government - Fogel, Kathy (Journal of International Business Studies, 2006)
Wealthy families, as opposed to small public shareholders, characterize ownership of the large corporate sectors of many countries around the world. This paper shows that greater oligarchic family control over large corporations is associated with worse social economic outcomes. It also correlates with more bureaucratic and more interventionist governments, and less developed financial markets. Further tests show that red tape, price controls, and the lack of shareholder rights protection are the paramount factors relating to the extent of family control of large firms. These results are broadly consistent with Olson and others who argue that economically entrenched wealthy insiders pursue rent-seeking activities to preserve the status quo, and that this increases corruption, and impedes growth.